An Introduction to Topological Data Analysis: Fundamental and Practical Aspects for Data Scientists - Chazal, Frédéric; Michel, Bertrand (Frontiers in Artificial Intelligence, 2021)
Topological Data Analysis (TDA ) is a recent and fast growing field providing a set of new topological and geometric tools to infer relevant features for possibly complex data. This paper is a brief introduction, through a few selected topics, to basic fundamental and practical aspects of TDA for non experts.